2022
DOI: 10.1002/adom.202101971
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Competition between Defect‐Trapped Exciton and Band‐Edge Exciton Photoluminescence in Monolayer Hexagonal WS2

Abstract: Monolayer transition‐metal dichalcogenides grown by chemical vapor deposition (CVD) always contain certain types of defects that dramatically affect their electronic and optical properties. For CVD‐grown hexagonal WS2 monolayer, complex photoluminescence (PL) patterns are commonly observed, but the defect‐related optical mechanisms are still not well understood. Here, by combining the optical and structural characterizations and ab initio calculations, the correlation between the patterned PL emission and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
(53 reference statements)
3
7
0
Order By: Relevance
“…The PL spectra of monolayer WS 2 treated by plasma exhibit only one peak around 2.0 eV, and the defect-induced PL peak is quite weak or even negligible. This result is consistent with the previous PL measurement at 295 K . It is indisputable that the defect state can lead to radiative recombination as shown in Figure c, but the defect-induced PL peak is more obviously to be detected at low temperature, as shown in Figure S4a–c.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The PL spectra of monolayer WS 2 treated by plasma exhibit only one peak around 2.0 eV, and the defect-induced PL peak is quite weak or even negligible. This result is consistent with the previous PL measurement at 295 K . It is indisputable that the defect state can lead to radiative recombination as shown in Figure c, but the defect-induced PL peak is more obviously to be detected at low temperature, as shown in Figure S4a–c.…”
Section: Resultssupporting
confidence: 92%
“…The far left depicts the mechanism in the WS 2 monolayer with V S or O 2S defects. The unoccupied defect state acts as the electron trap, opening up both the radiative and nonradiative recombination pathways. It is worth noting that at room temperature, there is sufficient thermal energy present to promote a portion of the trapped exciton population to the band edge, reducing the possibility of a defect-induced radiative recombination channel. , Therefore, in Figure c, the thinner arrow represents the radiative recombination channel introduced by the defect at room temperature. The nonradiative recombination mediated by defect states could occur at the same time as the band-edge recombination or in advance. , The right part depicts the mechanism in which an electron in the CBM directly recombines with a hole in the VB at the K point in both pristine and defective WS 2 monolayers.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the 2H phase shows a stronger PL compared to the 3R phase, indicating that the flower-like fine structure consists of the 3R phase . The PL quenching in this region could be due to defects or tungsten vacancies, which act as deep trap states, increasing the nonradiative recombination. ,, …”
Section: Resultsmentioning
confidence: 99%
“…41 The PL quenching in this region could be due to defects or tungsten vacancies, which act as deep trap states, increasing the nonradiative recombination. 38,39,41 Mechanical Properties. The preliminary AFM phase image in intermittent contact mode (see Figure 1b) gave indications that the domain formation is accompanied by a change in the mechanical properties of the WS 2 flake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation